Diabetes Mellitus Increased Mortality Rates More in Gender-Specific than in Nongender-Specific Cancer Patients: A Retrospective Study of 149, 491 Patients. (3rd June 2012) - Chiou, Wen-Ko; Hwang, Jawl-Shan; Hsu, Kuang-Hung; Lin, Jen-Der
Abstract : Aims . Hyperinsulinemia in overweight status, obesity, and type 2 diabetes mellitus (DM) is often accompanied by cancer. Gender is important in cancer epidemiology, clinical presentation, and response to therapy in different histological types of malignancy. Insufficient information is available concerning gender differences in DM with organ-specific and nonorgan-specific cancers. This study aimed to analyze gender differences in hospitalized cancer patients with or without type 2 DM. Methods . We retrospectively reviewed ten years of patients hospitalized in one institution, enrolling 36, 457 female and 50, 004 male cancer patients of which 5, 992 females and 8, 345 males were diagnosed as type 2 DM. Results . Statistically significant increases in incidence of type 2 DM were found in patients of both genders with pancreatic, liver, and urinary tract cancer. Increased incidence of type 2 DM was found in lung and hematologic malignancies in females and prostate cancer in males. Increases in mortality rates of females with type 2 DM (2.98%) were higher than those in males. DM increased mortality rates in gender-specific cancers from 1.91% (uterus, HR: 1.33) to 5.04% (ovary, HR: 1.49). Conclusion . Type 2 DM increased mortality of cancer patients of both genders, with higher increases in gender-specific than in nongender-specific cancers.